Search for resonant and nonresonant Higgs boson pair production in the b b ¯final state in proton-proton collisions at √s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2018)
Searches for resonant and nonresonant pair-produced Higgs bosons (HH) decaying respectively into `ν`ν, through either W or Z bosons, and bb are presented. The ¯ analyses are based on a sample of proton-proton collisions at √ s = 13 TeV, collected by the CMS experiment at the LHC, corresponding to an integrated luminosity of 35.9 fb−1 . Data and predictions from the standard model are in agreement within uncertainties. For the standard model HH hypothesis, the data exclude at 95% confidence level a product of the production cross section and branching fraction larger than 72 fb, corresponding to 79 times the standard model prediction. Constraints are placed on different scenarios considering anomalous couplings, which could affect the rate and kinematics of HH production. Upper limits at 95% confidence level are set on the production cross section of narrowwidth spin-0 and spin-2 particles decaying to Higgs boson pairs, the latter produced with minimal gravity-like coupling